A Trend of Influencer Marketing and Virtual Community - Arunchoknumlap, Paisarn (Journal of Business, Innovation and Sustainability (JBIS), 2023)
Today is the age of social media marketing, where customers need to consider many factors before choosing products and services. One of the most important factors is the influencer, which gives the consumer a crucial role in the process of making a purchase decision. According to the outbreak of COVID -19 has caused virtual marketing to quickly gain popularity. The academic article aims to 1) to explore the concept of influencer marketing, 2) to explore the concept of a virtual community, and 3) to explore the future trends of influencer marketing and virtual community through studies and documents. Literature research using the terms of "influencer," "influencer marketing," "influencer world," "social media," "virtual community," "virtual influencer," and "metaverse" via a search engine. Followed by analysis and discussion with influencer marketing and marketing technology specialists. Influencer marketing is a marketing strategy that relies on the power of influencers, or people who have followers on social media, to influence consumers' purchasing decisions. Virtual community is a new type of community that communicates with each other through computers or information technology networks as a communication medium. There are a large number of group members who come together to exchange information and social relationships, have a similar interest in a subject, regardless of time and place. Technology is essential trends that impact digital marketing and real-time marketing, which significantly impact and change business. Going forward, influencer marketing is applied to a digital character created in computer graphics software, then given a personality defined by a first-person perspective on the world, and made available on media platforms to effectively influence and reach the desired target audience through their digital persona. Virtual influencers allow a level of control and consistency that is impossible with human influencers. They do not age, they do not get sick, and they do not have the risk of scandalous personal behavior. In addition, virtual influencers can be programmed to have specific skills or talents that align with the brand's message, allowing them to promote products or services even more effectively. However, technological trends such as virtual marketing are of greater importance, especially in the era of the COVID-19 pandemic. The virtual influencer has become a driving force that is helping the influencer marketing industry grow and retain customers, encompassing virtual events, digital marketing and e-commerce.